PERLINDUNGAN HUKUM BAGI NASABAH SEBAGAI DEBITUR ATAS PENGGUNAAN PERJANJIAN BAKU DALAM PERJANJIAN KREDIT BANK - Dewi, Ni Putu Arista Ratna; Utami, Putu Devi Yustisia (Kertha Negara : Journal Ilmu Hukum, 2023)
The purpose of this article is to identify and analyze legal protection for customers as debtors for using standard agreements in bank credit agreements. This study uses normative legal research methods with a legal instrument or legal product approach and a legal concept analysis approach. The sources of legal materials are Primary Legal Materials in the form of regulations relating to standard agreements and bank credit agreements and the secondary legal materials used are obtained from law books and scientific journals related to the problem under study. The writing technique for the article uses literature study by analyzing books that focus on secondary data and written law. The results of the study show that legal protection for customers for the use of standard agreements in bank credit agreements has been regulated preventively in the provisions of Article 18 UUPK, articles 21 and 22 POJK Number 1/POJK.07/2013 concerning Consumer Protection in the Service Sector, and also regulated in the SE. Financial Services Authority Number 13/SEOJK.07/2014 Concerning Standard Agreements while repressively regulated in Articles 29 and 30 paragraph (1) of the OJK Law besides that it is also regulated in Article 40 POJK Number 1/POJK.07/2013 concerning Consumer Protection in the Service Sector Finance and Article 4 letter a POJK Number 1/POJK.07/2014 concerning Alternative Dispute Resolution Institutions in the Financial Services Sector.